Pengaruh Estetika Kemasan Terhadap Keputusan Pembelian Produk Skincare Lokal di Kalangan Mahasiswa - Alya Nasyani Purba; Stephania Deza E Siahaan; Didi Haryadi; Mahda Aidil Hanafi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the influence of packaging aesthetics on the purchasing decisions of university students who use local skincare products. As competition in the Indonesian skincare market intensifies, visual elements such as color composition, container shape, typography clarity, and overall design harmony increasingly shape consumer perception. A quantitative descriptive method was applied, involving 26 respondents selected through purposive sampling, with data collected via a Likert-scale questionnaire that measured perceptions of packaging aesthetics and purchasing decisions. The findings reveal that color composition and container shape are the most influential aesthetic components, indicating the strong role of visual cues in attracting initial consumer attention. Meanwhile, purchasing decision indicators show that visual appeal contributes significantly to early interest and product comparison, although it is not the dominant factor in motivating consumers to try unfamiliar products. Overall, the results underline that aesthetic packaging enhances perceived value, strengthens brand credibility, and reinforces emotional associations that guide purchasing preferences among young consumers. These insights highlight the strategic importance of visual design in the marketing of local skincare products.